All we needed to say : poems about school from Tanya and Sophie - Singer, Marilyn; Clark, Lorna, 1961- (New York : Atheneum Books for Young Readers, 1996)
A collection of poems in which two girls, Tanya and Sophie, express their differing opinions on gym class, library hour, and other aspects of a day at school.
Elem. School Library Collection
School Library Journal
Publisher's Weekly
4.5
3-6
Keywords: Schools -- Juvenile poetry; Children's poetry, American; Schools -- Poetry; American poetry; Schools -- Poetry